Religion and slavery in America through Claude Fohlen’s Histoire de l'esclavage aux Etats-Unis: Varia (Cahiers Africains de rhétorique, 2025)
The history of America at large and that of slavery in particular cannot be told without sound reference to religion. Indeed, the practice of Christianity imposed by the masters was a key tool for to get the slaves busy when they were not at work, on Sundays mainly, and white pastors resorted to interpretation of the bible aiming at getting the black slaves to accept and adapt to their condition. Yet, from adaptation to the white man’s religion, the black slaves found motives for fight and resistance. Claude Fohlen’s L’Histoire de l’Esclavage en Amérique has explored the functioning of slavery in America, along with the importance of religion in the process. The present paper seeks to highlight the meaning of religion to both the slave master and the slaves themselves, and how it served both the white master’s control over slaves, and the slaves’ fight for emancipation. The study has been conducted under the New Criticism theory, an approach that focuses primarily on the text itself, avoiding outside influences such as historical and biographical information that might drive the reader from the essential meaning of the text.